2018
DOI: 10.1021/acs.inorgchem.8b01625
|View full text |Cite
|
Sign up to set email alerts
|

A Spin-Crossover Molecular Material Describing Four Distinct Thermal Pathways

Abstract: Spin-crossover (SCO) molecular solids are valued switchable materials for their common abrupt and reversible thermal transitions, large thermal hysteresis, or guest-dependent effects. These properties usually involve crystallographic transitions coupled to the SCO events. These phenomena are of great value for the understanding of solid-state transformations and also for exploiting them. We present here a lattice of the complex [FeL(bbp)](ClO) (1; L and bbp are tris-imine ligands) featuring an unprecedented ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…18,19 Consequently, it is rather common to find polymorphs or solvatomorphs of the same SCO complex displaying completely different magnetic transitions. [20][21][22][23] Moreover, other solid state phenomena like phase transitions, solvent absorption/desorption or order disorder processes might occur concomitantly to the spin transition, occasionally leading to multiple SCO pathways, 24 reverse SCO, 25 or a spin state blocking along the entire range of temperatures. 26,27 As a result, the evaluation of ∆ needs to account for the energetic impact of such processes on the SCO.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Consequently, it is rather common to find polymorphs or solvatomorphs of the same SCO complex displaying completely different magnetic transitions. [20][21][22][23] Moreover, other solid state phenomena like phase transitions, solvent absorption/desorption or order disorder processes might occur concomitantly to the spin transition, occasionally leading to multiple SCO pathways, 24 reverse SCO, 25 or a spin state blocking along the entire range of temperatures. 26,27 As a result, the evaluation of ∆ needs to account for the energetic impact of such processes on the SCO.…”
Section: Introductionmentioning
confidence: 99%
“…This quasi-exclusive formation of heteroleptic adducts has been proven as a prolific source of new compounds with very diverse properties. 17,18 In previous reports, we showed that the solvent-free perchlorate salt of the homoleptic iron(II) complex of the ligand 1bppCOOH (2,6-bis(1H-pyrazol-1-yl)isonicotinic acid, Scheme 1) exhibits a hysteretic (3 K) abrupt thermal spin transition at high temperatures (380 K) affected by the presence of a linear network of hydrogen-bonded complexes. 19 Moreover, it has been proved that the introduction of a carboxylic acid group on the 4-pyridyl position promotes the formation of a polynuclear metal complex 20 and could facilitate the anchoring to metal-oxide surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Results for this variable-temperature study are: 1.441 (1) at 18 K, 1.439 (1) at 78 K, and 1.436 (1) Å at 158 K. A search of the Cambridge Structural Database (Groom et al, 2016; Conquest, Version 2.0.1) for X-ray diffraction studies of perchlorate distances in the temperature range 283-303 K having no disorder or errors, powder data excluded, and with an R 1 value < 5%, yielded 3138 hits and a mean distance of 1.405 Å ; in the range 160-180 K, gave 845 entries with a mean value of 1.426 Å ; and in the range 80-100 K, gave 1217 entries with a mean value of 1.436 Å . An extensive synchrotron X-ray investigation into a spin-crossover solid produced data at temperatures ranging between 30 and 360 K with four perchlorate anions (Bartual-Murgui et al, 2018). The two iron complexes in the crystal have H-atom donors and it is apparent that the O-atom acceptors have slightly longer Cl-O bonds.…”
Section: Figurementioning
confidence: 99%